Pigeons retain partial memories of homing paths years after learning them individually, collectively or culturally. Issue 1963 (24th November 2021) - Collet, Julien; Sasaki, Takao; Biro, Dora
Abstract : Memory of past experience is central to many animal decisions, but how long specific memories can influence behaviour is poorly understood. Few studies have reported memories retrieved after several years in non-human animals, especially for spatial tasks, and whether the social context during learning could affect long-term memory retention. We investigated homing pigeons' spatial memory by GPS-recording their homing paths from a site 9 km from their loft. We compared solo flights of naive pigeons with those of pigeons that had last homed from this site 3–4 years earlier, having learnt a homing route either alone (individual learning), together with a naive partner (collective learning) or within cultural transmission chains (cultural learning). We used as a control a second release site unfamiliar to all pigeons. Pigeons from all learning treatments outperformed naive birds at the familiar (but not the unfamiliar) site, but the idiosyncratic routes they formerly used several years before were now partially forgotten. Our results show that non-human animals can use their memory to solve a spatial task years after they last performed it, irrespective of the social context during learning. They also suggest that without reinforcement, landmarks and culturally acquired 'route traditions' are gradually forgotten.